LARGE FEUDAL LANDOWNERSHIP AND FORMS OF LAND TENURE IN MOUNTAINOUS DAGESTAN IN THE 18TH - FIRST HALF OF THE 19TH CENTURIES - Aliev, B G (History, Archeology and Ethnography of the Caucasus, 2016)
The author of the article considers large feudal landed estates and feudal land rent in Mountainous Dagestan in the late feudal period. There were two khanates – Avar and Kazikumukh – in Mountainous Dagestan. Analysis of available sources and literature shows that the largest landowners in these feudal landed estates were their owners, the khans. They owned all kinds of land – pastures,hayfields, arable and forest areas. But two main kinds of land that they possessed were pasture mountains and pasture areas, which were located not only within the territory of the khanates, but also in the territory of different societies. The khans had large income due to their ownership of land, especially of pasture mountains, which were in the use of entire rural communities. In both khanates there were villages, inhabited by dependent peasants – rayats. The dependent peasantry carried out various duties for the use of the khan’s lands. The article presents specific examples concerning several villages of the khanates, the population of which had to pay various fees and duties to the khans.
Keywords: large feudal estate; Avar Khan; Kazikumukh Khan; types of land; pasture mountains; arable areas; fees and duties of peasants.